Immunological and microbiological activity of Davilla elliptica St. Hill. (Dilleniaceae) against Mycobacterium tuberculosis - Lopes, Flávia Cristine Mascia [UNESP]; Placeres, Marisa Campos Polesi [UNESP]; Jordão Junior, Cleso Mendonça [UNESP]; Higuchi, Célio Takashi [UNESP]; Rinaldo, Daniel [UNESP]; Vilegas, Wagner [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2007)
Mycobacterium tuberculosis is responsible for over 8 million cases of tuberculosis (TB) annually. Natural products may play important roles in the chemotherapy of TB. The immunological activity of Davilla elliptica chloroform extract (DECE) was evaluated in vitro by the determination of hydrogen peroxide (H2O2), nitric oxide (NO), and tumor necrosis factor-alpha (TNF-alpha) release in peritoneal macrophages cultures. DECE was also tested for its antimycobacterial activity against M. tuberculosis using the microplate alamar blue assay. DECE (50, 150, 250 µg/ml) stimulated the production of H2O2 (from 1,79 ± 0,23 to 7,27 ± 2,54; 15,02 ± 2,86; 20,5 ± 2,1 nmols) (means ± SD), NO (from 2,64 ± 1,02 to 25,59 ± 2,29; 26,68 ± 2,41; 29,45 ± 5,87 µmols) (means ± SD) and TNF-alpha (from 2,44 ± 1,46 to 30,37 ± 8,13; 38,68 ± 1,59; 41,6 ± 0,90 units/ml) (means ± SD) in a dose-dependent manner and also showed a promising antimycobacterial activity with a minimum inhibitory concentration of 62,5 µg/ml. This plant may have therapeutic potential in the immunological and microbiological control of TB.
Keywords: Davilla elliptica; antimycobacterial activity; immunological activity